Numerical method for Volterra integro-differential equation by Taylor Collocation - CHIKOUCHE, Samah Racha (University of M'sila, 2023)
In this thesis, we have solved the linear Volterra Integro-Differential equation od the second kind numerically,using the Taylor Collocation method which converts the equation into an algebraic linear system .We have strengthened by examples for proved the accuracy of the method.
Keywords: Volterra linear Integro-Differential equation of the second kind , Taylor Collocation method .